Longitudinal transformation of mitochondrial metabolism during neurogenesis - Donghoon Lim; Sewon Park; Jong Seung Lee; Hyo Jin Gwon; Yunwoo Nam; Suhyuk Choi; Jongwon Kim; Yeonsu Kim; Geonwoo Park; Woo Yang Pyun; Hyun Woo Park; Seung-Woo Cho; et al. (Proceedings of the National Academy of Sciences, 2025)
Neural stem cells (NSCs) are valuable in the quest to conquer neurodegenerative diseases due to their capability to reconstruct the damaged neuronal networks. However, deep understanding of the intercellular signaling mechanism controlling the lineage and fate of the stem cells is required before potential clinical applications. Here, we applied nondestructive and label-free electrochemical methods for the longitudinal tracking of NSC respiratory metabolism. Sharp change in the oxygen utilization pattern was observed concomitant to stemness loss and onset of differentiation, suggesting metabolic reprogramming in the transition. Intra- and extracellular profiling of mitochondrial metabolites revealed molecular preference in the extracellular transport rates. Electrochemical emulation of the metabolite release pattern induced acceleration of neurite growth in nearby cells, suggesting paracrine signaling system mediated by mitochondrial metabolites.